Analisis Sentimen Kebijakan Protokol Kesehatan Pada Masa Pandemi Di Media Sosial Facebook dengan Crowdtangle - Bramantyo, Ade Rizki; Pratama, Ahmad R. (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Various policies have been made by Indonesian Government to handle the spreading of COVID-19. Indonesian Government released several rules called health protocol that regulate public activities during the pandemic. The government policy of releasing those rules created different public opinions. Sentiment analysis was conducted to know how people see and think about health protocol. This study analyzed the public reactions on Facebook posts about health protocol from government account and news portal account. The data was collected using CrowdTangle with “protokol kesehatan”, “wajib masker”, and “jaga jarak” chosen as keywords. CrowdTangle collects useful Facebook data including reactions (love, care, sad, angry) that represent a sentiment, message, and total interactions. The result of the sentiment analysis showed that public gave more positive reactions than negative reactions to health protocol posts. Based on the nonparametric statistic tests (Mann-Whitney test and Kruskal-Wallis test) results, the account types (government account and news portal account) affected the public reactions and the total number of interactions. Moreover, the total number of interactions was also influenced by the post types (link, status, photo, and video).